An experience of collaboration using a PaaS for the smarter university model. (December 2015) - Coccoli, Mauro; Maresca, Paolo; Stanganelli, Lidia; Guercio, Angela
Abstract: In this paper we continue our previous research on the development of the current model of higher education, which pointed out that the labor market is looking for people with competencies and skills reflecting a T-shape model. As a consequence, universities should include a wider mix of disciplines in the curricula of their courses. Hence, to overcome existing criticisms and to provide some suggestions on how to enhance universities׳ performances, we thought of education as a process with inputs, outputs, and relevant dependencies. We called such a university a "smarter university" in which knowledge is a common heritage of teachers and students. In our research the smarter university model is based on a smart-city-like model, due to the fact that next generation networks and relevant services are going to be more and more integrated with existing infrastructure and information management systems. Thus, it is mandatory that smart solutions are the most prominent assets of modern university environments to improve the effectiveness of higher education. In this paper, we report the experimental results from a specific case study of collaboration between industry and university, which could be used as a reference for the definition of patterns to be applied in the redesign of the current education systems, even though the experiment refers to a technological application scenario.